Multiple pulmonary metastases from asymptomatic benign intracranial meningioma: case report - Ušinskienė, Jurgita; Letautienė, Simona Rūta; Šestelinska, Evelina; Neverauskienė, Laura; Ročka, Saulius (Lietuvos chirurgija, 2016)
Background This case presents unexpected association between diseases and symptoms. We believe that it should compel clinicians to rethink the known behaviors of the benign tumors, in particular meningioma which can gain independent metastatic potential. This report aims to increase the awareness of clinicians toward patients with this unusual and clinically isolated pattern, because metastases can remain misdiagnosed for a long period of time. This case contributes to medical knowledge, diagnostic and prognostic approaches. This is also the first case of metastatic meningioma reported in Lithuania. Case presentation We report a 66-year-old woman who presented with persistant productive cough, dyspnea, fever and weakness during physical activity. Chest radiographs revealed multiple small round shaped pulmonary nodules. Thoracoscopic resection and histopathology showed a benign meningioma. Magnetic resonance imaging scan of the brain demonstrated a small dural based mass in the left pontocerebellar angle connected with deep dilated cerebral venous network and superior petrosal sinus. Morphological findings of the session were consistent with a World Health Organization grade I fibrous meningioma. Conclusion Meningiomas are usually non-invasive tumors and do not metastasize and hence, are perceived as benign tumors. Patients with this uncommon and clinically isolated pattern of metastases can remain misdiagnosed for a long period of time, due to unexpected behavior of this particular tumor. This case report denies most of the criteria of possible risk factors for the development of metastases from a meningioma what allows to consider it as tumor with unpredictable behavior.
Keywords: case report; meningioma; benign; asymptomatic; metastases